La mujer española y el discurso moralista en Nueva España (s. XVI- XVII) - Alberto Baena Zapatero (Nuevo mundo - Mundos Nuevos, 2008)
In New Spain, the moralists, in spite of their peninsular or creole origin, focused their arguments on the minority group which was most likely to be subject of prejudice: the women. The convergence between public and private life gave particular importance to the weak nature of the female population, as it was widely believed that the excesses of women could lead to political decadence for the Kingdom. The works of these religious men give an insight view of the patriarchal model imposed on women, and their criticisms show us how this paradigm could, on certain occasions, be softened and infringed in practice. Their moral aims focused on two main areas: (i) the upholding of a more cloistered, religious life for women to counterbalance the believed idleness of creole ladies, prohibiting their attendance to parties, to theatrical plays, and their attendance at church only to show off; and (ii) the condemnation of opulent and ostentatious lives among members of the most privileged sectors.